Caught napping - Anonymous (Salt Lake City, UT : Project Gutenberg, 2023)
"Caught Napping" by Anonymous is a satirical novel written during the mid-19th century, likely in the Victorian era. The book explores themes of Anglicanism, ritual, and cultural misunderstandings through the character of a 19th-century Anglican priest who finds himself inexplicably transported to the catacombs of ancient Rome. The narrative combines humor and a critical look at religious practices, presenting a clash of values between historical Christianity and the author's contemporary beliefs. The story follows Edward Starch, the Anglican priest, as he navigates the challenges of his unexpected situation. After falling asleep in his study, he awakens in the catacombs where he is mistaken for a martyr and is confronted with the practices of early Christianity, which starkly differ from his own beliefs. Throughout his adventures, Edward grapples with issues of ritualistic worship, his identity as an Anglican, and the absurdities of the religious customs of both his time and the past. As he attempts to defend his views and seek a way back to his own time, he encounters various characters that highlight the humor and contradictions inherent in religious practices, culminating in a surreal twist when he finally wakes up in his study, realizing it was all a remarkable dream. (This is an automatically generated summary.)
A satire on the Church of England.
Release date is 2023-01-14
Charlene Taylor, Bob Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Church of England -- Humor